Нормативно-Политические Вопросы Обращение С Обеспечением Низкого Образования В Индонезии (Policy In Handling The Low Education Relevance In Indonesia) - Indrayanto, Indrayanto; Germanovna, Smyshlyaeva Larisa (Jurnal Cita Hukum, 2020)
AbstractThe problem of Human Resources (HR) in Indonesia is becoming increasingly complex, this is reflected in the large number of formal education graduates from various levels who are not absorbed in the world of work. Many factors cause this to happen, including the mismatch between HR competencies and the labor market, the growth of the workforce is greater than the availability of available employment and population distribution between regions is not evenly distributed. If you look at the achievements of Indonesian tertiary education graduates, many of Indonesian tertiary education graduates are slow to get jobs, this shows that there is a broken link between higher education and the world of work. Higher education has not been able to produce graduates with high selling prices armed with the knowledge they have learned even though in general higher education graduates have greater employment opportunities than high school or lower level graduates. Many realities on the ground show that the quality of Indonesian people as a potential resource still does not meet expectations. This happens because of the low quality of education in Indonesia. By fulfilling good educational needs, the students will get benefits and can improve the quality of life of the knowledge they have, so that after completing their education, they can get decent jobs or create quality jobs. Indonesia's education world must start to build links with the world of work, so that the world of work responds to graduates produced in accordance with what the world of work wants; this paradigm must be understood and built by the Indonesian government. Education transformation is needed so that education is able to produce reliable and resilient human resources; education and educators must be improved.Keyword: Education; Policy; Indonesia Abstrak:Permasalahan Sumber Daya Manusia (SDM) di Indonesia menjadi semakin kompleks, hal ini tercermin dengan banyaknya para lulusan pendidikan formal dari berbagai jenjang yang tidak terserap dalam dunia kerja. Banyak factor yang menyebabkan hal ini terjadi, diantaranya yaitu ketidaksesuaian antara kompetensi SDM dengan pasar kerja, pertumbuhan angkatan kerja lebih besar dari ketersediaan lapangan kerja yang ada serta ditribusi penduduk antar daerah belum merata. Jika melihat dari capaian para lulusan pendidikan tinggi Indonesia, banyak dari lulusan perguruan tinggi di Indonesia lambat mendapatkan pekerjaan, Ini menunjukkan terdapatnya mata rantai yang putus antara pendidikan tinggi dan dunia kerja. Perguruan tinggi belum mampu menghasilkan lulusan dengan harga jual yang tinggi berbekal dengan ilmu yang telah dipelajari meskipun secara umum lulusan pendidikan tinggi memiliki peluang kerja lebih besar dibanding lulusan tingkat SMA ataupun lebih rendah lagi. Banyak realita di lapangan yang menunjukkan bahwa kualitas masyarakat Indonesia sebagai sumber daya yang potensial masih belum memenuhi harapan. Hal ini terjadi dikarenakan rendahnya kualitas pendidikan di Indonesia. Dengan terpenuhi kebutuhan pendidikan yang baik, siswa-siswa peserta didik tersebut akan mendapatkan manfaat dan dapat meningkatkan kualitas hidup dari pengetahuan yang dimiliki, sehingga setelah menyelesaikan pendidikannya, mereka dapat memperoleh pekerjaan yang layak atau menciptakan lapangan kerja yang berkualitas. Dunia pendidikan Indonesia haruslah memulai untuk membangun mata rantai dengan dunia kerja, sehngga respon dunia kerja terhadap lulusan yang dihasilkan sesuai dengan yang diinginkan dunia kerja; paradigma seperti ini harus dipahami dan dibangun oleh pemerintah Indonesia.Transformasi pendidikan diperlukan agar pendidikan mampu menghasilkan sumber daya manusia yang handal dan tangguh; pendidikan dan tenaga pendidik harus ditingkatkan.Kata Kunci: Pendidikan; Kebijakan; Indonesia АннотацияПроблема человеческих ресурсов в Индонезии становится все более сложной, что отражается в большом количестве выпускников формального образования разных уровней, которые не поглощены работой. Это обусловлено многими факторами, в том числе несоответствием между компетенциями в области людских ресурсов и рынком труда, рост рабочей силы превышает доступную занятость, а распределение населения между регионами распределяется неравномерно. Если вы посмотрите на достижения индонезийских выпускников высших учебных заведений, многие выпускники высших учебных заведений в Индонезии не могут найти работу, и это показывает, что существует разрывная связь между высшим образованием и миром труда. Высшее образование не смогло подготовить выпускников с высокими отпускными ценами, вооруженных знаниями, которые они узнали, хотя в целом выпускники высших учебных заведений имеют более широкие возможности трудоустройства, чем выпускники старших классов. Многие реалии на местах показывают, что качество индонезийского народа как потенциального ресурса все еще не соответствует ожиданиям. Это происходит из-за низкого качества образования в Индонезии. Выполняя хорошие образовательные потребности, студенты получают преимущества и могут улучшить качество жизни знаний, которые они имеют, так что после завершения обучения они могут получить достойную работу или создать качественную работу. Мир образования Индонезии должен начать строить связи с миром труда, чтобы мир труда реагировал на выпускников, произведенных в соответствии с тем, что хочет мир труда; эта парадигма должна быть понята и построена правительством Индонезии: трансформация образования необходима для того, чтобы образование могло производить надежные и устойчивые человеческие ресурсы; образование и воспитатели должны быть улучшены.Ключевые слова: образование; Политика; Индонезия